Transflective liquid crystal displays. - Ge, Zhibing, ....-; Wu, Shin-Tson, ....- (Chichester : Wiley, 2010)
1 Device Concept of Transflective Liquid Crystal Displays 1.1 Overview 1.2 Polarizers 1.3 LC Alignment 1.4 Compensation Films 1.5 Reflectors 1.6 Backlight 1.7 Summary References 2 Device Physics and Modeling 2.1 Overview 2.2 Modeling of LC Directors 2.3 Modeling of LC Optics 2.4 Device Physics of Transflective LCDs 2.5 Summary Appendix 2.A References 3 Light Polarization and Wide Viewing Angle 3.1 Poincar? Sphere for Light Polarization in LCDs 3.2 Compensation of Linear Polarizers 3.3 Compensation of Circular Polarizers 3.4 Summary References 4 Wide-view Transflective LCDs 4.1 Overview 4.2 Transflective LCD using MVA Mode 4.3 Transflective LCD using IPS Mode 4.4 Summary References 5 Color Sequential Mobile LCDs 5.1 Overview 5.2 Color Sequential Driving Schemes 5.3 Fast-response LC Modes 5.4 Fast-response Transflective LCDs 5.5 Summary References 6 Technological Perspective 6.1 Unique Role of Transflective LCDs 6.2 Emerging Touch Panel Technology 6.3 Summary
Keywords: LCD (Liquid Crystal Displays).